Synthesis, Characterization, and Application of Europium(III) Complexes as Luminescent Markers of Banknotes - Macrino,Clebson J. (2021)
In this work, three complexes were synthesized from the trivalent europium ion (EuIII), using the picrate anion (pic), and delta-valerolactam (DVL), epsilon-caprolactam (EPK), and oenantholactam (OEN). The synthesized complexes [Eu(pic)3·(DVL)3], [Eu(pic)3·(EPK)3], and [Eu(pic)3·(OEN)3] were studied as luminescent markers for application as security elements in Brazilian banknotes. All complexes showed red color emission with absorption at 397 nm and emission at 614 nm. Qualitative luminescence tests were performed on R$10, R$20, R$50, and R$100 Brazilian banknotes. The complexes were applied on the surface of the banknotes and were exposed to different wavelengths of 254, 312, 365, and 320-400 nm. The chemical profiles of the complexes were identified on the banknotes employing the laser desorption ionization mass spectrometry (LDI (±) MS) technique. Generally, tests were promising, and can thus provide a simple, fast, and easy method to identify the authenticity of questioned documents, with an average cost of R$0.65 per mg.